El Niño and Schools in Peru: What Do We Know About the Impacts of the Last Three Events? - Etesse, Manuel (2024)
This paper focuses on the relationship between education and the El Niño phenomenon (FEN). Through a documentary study, it aims to contribute to the emerging field of research on education and disasters. The ENP, a significant climatological event in South America, manifests along the northern coast of Peru and has critical consequences in various sectors, including education. The research systematizes existing knowledge on the effects of the last three extreme ENP events (1982, 1997, 2017) on Peruvian schools within the framework of three approaches: disaster education, school disaster management, and disaster impact on schools. Two specific objectives are proposed: 1. to identify the production of knowledge on ENP and education, and 2. to explore the impacts reported in institutional and journalistic Peruvian publications. The methodology is exploratory, based on a thorough review of secondary academic and non-academic sources. Only one article was found in Peruvian academic journals and few theses on the subject. The reported impacts of ENP on Peruvian education include significant material damages, adverse effects on school infrastructure, delays in the school calendar, and adverse effects on the health of the school population. The document discusses the limitations of the data on impacts and the approaches to education and disasters.